Improving Silvofishery Management Through Seedling Growth – Environment Quality Dynamic Relation Analysis - Endah Dwi Hastuti; Rini Budi Hastuti (Biosaintifika: Journal of Biology & Biology Education, 2017)
Mangrove plants are sensitive to environment condition. This research aimed to analyze the linkages of mangrove growth and environment dynamics and to estimate the growth of mangrove along with the environment dynamics. The research was conducted through the field experiment by the plantation of A. marina in silvofishery pond canals. Data collection was conducted for 18 months with 3 months observation interval. The environment variables observed including temperature, salinity, turbidity, pH, dissolved oxygen, TSS, sediment organic matter, nitrogen and phosphorus, and the growth of mangrove seedling. Analysis was conducted through regression and modelling with Powersim software. The result showed that the height growth was affected by dissolved oxygen, temperature, salinity, turbidity and pH, while the diameter growth was affected by TSS concentration. Inversely, the growth of mangrove also had a significant effect on temperature, change of organic matter and nutrient sediment concentration. Simulation showed that the height and diameter growth rates of A. marina seedling were dynamically changed among periods. Simulated seedling growth for one year forecast resulted in the rate of 0.115024 to 0.282294 cm/day for height and 0.001287 to 0.006031 cm/day for diameter. The simulation also indicated the continuous accumulation of organic matter and nitrogen over time. This research concluded that under limited environment dynamic, the growth of mangrove could be estimated. This model is a novelty in ecological studies. This research might initiates the more advanced ecological studies. Systematic estimation of ecosystem behaviour could be applied to formulate the best management practices, particularly in the silvofishery activities.